Financial sector consolidation and competition in Malaysia: an application of the Panzar-Rosse method - Sufian, Fadzlan; Habibullah, Muzafar Shah (Emerald Group Publishing Limited, 2013)
Purpose – The purpose of the present study is to investigate the effect of consolidation on Malaysian banking sector’s market structure and competition. Design/methodology/approach – The paper employs the Panzar-Rosse (P-R) method to compute the H-statistics of the Malaysian banking sector. Findings – The results from the P-R method indicate positive H-statistics ranging from 0.680-0.747 under the TREV estimation and 0.547-0.714 under the TINT estimation. The Wald x2 test statistics seem to reject the market structure of monopoly or perfect competition hypothesis. The results clearly indicate monopolistic competition behavior in the Malaysian banking sector. During the period under study, the paper finds evidence of greater competition in the overall market segment, which is comprised of operating income from fee and commission based products compared to the traditional interest-based market. Research limitations/implications – The empirical findings from this study clearly indicate that competitive behaviour of banks may be explained by factors other than the number of banks operating in the banking sector and their levels of concentration. However, the results need to be interpreted with caution since the liberalization and deregulation of the Malaysian banking sector remains an ongoing process. Originality/value – Despite substantial studies performed to examine the impact of consolidation on banks’ competitive behaviour, these studies have concentrated mainly on the banking sectors of the western and developed countries. On the other hand, empirical evidence on the developing countries banking sectors is relatively scarce.